Comparison of PSO, DE and Hybrid DE-PSO for LFC of Wind Power Systems - rodik wahyu indrawan; herlambang setiadi; muhammmad Aldo Setiawan; Rizki Putra Prastio (Faculty of Advanced Technology and Multidiscipline Universitas Airlangga, 2022)
Abstract—This paper investigates the performance of particle swarm optimization (PSO), differential evolution (DE), and hybrid particle swarm optimization- differential evolution (HDEPSO) for solving load frequency control (LFC) problems. Wind power systems LFC model is used to compare the performance of PSO, DE and HPSODE for solving LFC problems. All the simulation are carried out in MATLAB/SIMULINK environment. From the simulation results, it is noticeable that by designing LFC of wind power system using HPSODE, the overshoot and settling time of the wind power system can be reduced and accelerated.